Inferential procedures for log logistic distribution with doubly interval censored data - Loh, Yue Fang; Arasan, Jayanthi; Midi, Habshah; Abu Bakar, Mohd Rizam (2017)
The log logistic model with doubly interval censored data is examined. Three methods of constructing confidence interval estimates for the parameter of the model were compared and discussed. The results of the coverage probability study indicated that the Wald outperformed the likelihood ratio and jackknife inferential procedures.